Administrators' practices of Islamic leadership in selected Islamic schools within Kuala Lumpur : teachers' perspectives - Said, Deka Hassan (Kulliyyah of Education, International Islamic University Malaysia, 2019)
Research concerning Islamic school leadership from teachers' perspectives is very scarce in which most research only takes into consideration the account of administrators. Furthermore, the use of Dr. Saleh's comprehensive framework for educational administration has not been previously employed to assess Islamic school leadership practices. Thus, the purpose of this study was to explore and analyse the practices of Islamic leadership from the perspective of both primary and secondary Islamic school teachers. Secondly, this study also sought to assess whether Dr. Saleh's four tier framework consisting of the Personal, Interpersonal, Managerial and Organizational levels of Islamic leadership holds relevance in an Islamic school setting. A phenomenological design was employed in which six teachers from three private Islamic schools in Kuala Lumpur, Malaysia, partook in a structured open-ended interview. The participants involved three males and three females, in which two were from South East Asia, three from Africa, and one from North America. With the application of Dr. Saleh's framework of Islamic educational administration, an inductive analysis of the data was applied in which the twenty-seven prescribed principles were examined in congruence with teachers' accounts of leadership practices within their respective schools. Teachers mentioned twenty-two out the twenty-seven principles outlined in Saleh's framework in which some characteristics were positively attributed to administrators while others were mentioned with negative implications. The findings assert that the perceptions held by teachers of the three designated Islamic schools follow a consistent pattern in which they mostly disapprove of administrative practices due to its observed incompatibility with the expected Islamic principles of governance outlined in Saleh's four-tier framework. Amongst the most prevalent issues, teachers have stated the following needs in which administrators ought to practice: lead with accountability, receptivity to various perspectives, communicate plans with transparency and a conscientious presence during school hours. The study concluded with some recommendations for administrative practices and also for further research.